Pembaharuan Hukum Waris Islam di Turki - Umar Faruq Thohir; Ramdan Wagianto (Asy-Syari’ah : Jurnal Hukum Islam, 2019)
It is inevitable that a legal enactment, or reform of Islamic family law in various Muslim countries or countries with a majority Muslim population in the world. This is because the existing law (valid) is still not revealed or has been revealed but is considered not in accordance with the era anymore, due to the different “context” between the past and the present. As Anderson said, Islamic law in Islamic countries was not static at all. The form of renewal that is carried out differs from country to country. First, there are some countries that carry out reforms in the form of laws. Second, there are some countries that carry out reforms based on the decree of the president or king. Third, there are some countries that carry out reforms in the form of judicial provisions. The country of Turkey is the first country to carry out renewal in family law. Updates are carried out in the form of laws. For Turkish Muslims, Hanafi is a school that underlies the religious life formally until 1926, before the existence of legislation legislation that was eclectically codified. The Islamic Civil Law or what is called ¬Majallat al-Ahkâm al-liAdliyah, which most of the material is based on Hanaf madîî actually has been prepared in Turkey since 1876, although it is not comprehensive, because it does not include family law and inheritance law. Keywords: reform of Islamic, Waris, and Turkish Muslims